Glycogen storage and muscle glucose transporters (GLUT-4) of mice selectively bred for high voluntary wheel running - Gomes, Fernando R. [UNESP]; Rezende, Enrico L.; Malisch, Jessica L.; Lee, Sun K.; Rivas, Donato A.; Kelly, Scott A.; Lytle, Christian; Yaspelkis III, Ben B.; Garland Jr., Theodore (The Company of Biologists, 2009)
To examine the evolution of endurance-exercise behaviour, we have selectively bred four replicate lines of laboratory mice (Mus domesticus) for high voluntary wheel running ('high runner' or HR lines), while also maintaining four non-selected control (C) lines. By generation 16, HR mice ran ∼2.7-fold more than C mice, mainly by running faster (especially in females), a differential maintained through subsequent generations, suggesting an evolutionary limit of unknown origin. We hypothesized that HR mice would have higher glycogen levels before nightly running, show greater depletion of those depots during their more intense wheel running, and have increased glycogen synthase activity and GLUT-4 protein in skeletal muscle. We sampled females from generation 35 at three times (photophase 07:00 h-19:00 h) during days 5-6 of wheel access, as in the routine selection protocol: Group 1, day 5, 16:00 h-17:30 h, wheels blocked from 13:00 h; Group 2, day 6, 02:00 h-03:30 h (immediately after peak running); and Group 3, day 6, 07:00 h-08:30 h. An additional Group 4, sampled 16:00 h-17:30 h, never had wheels. HR individuals with the mini-muscle phenotype (50% reduced hindlimb muscle mass) were distinguished for statistical analyses comparing C, HR normal, and HR mini. HR mini ran more than HR normal, and at higher speeds, which might explain why they have been favored by the selective-breeding protocol. Plasma glucose was higher in Group 1 than in Group 4, indicating a training effect (phenotypic plasticity). Without wheels, no differences in gastrocnemius GLUT-4 were observed. After 5 days with wheels, all mice showed elevated GLUT-4, but HR normal and mini were 2.5-fold higher than C. At all times and irrespective of wheel access, HR mini showed approximately three-fold higher [glycogen] in gastrocnemius and altered glycogen synthase activity. HR mini also showed elevated glycogen in soleus when sampled during peak running. All mice showed some glycogen depletion during nightly wheel running, in muscles and/or liver, but the magnitude of this depletion was not large and hence does not seem to be limiting to the evolution of even-higher wheel running.
Keywords: Adaptive plasticity; Artificial selection; Experimental evolution; GLUT-4; Glycogen; Phenotypic plasticity; Selection limit; Voluntary exercise; glucose transporter 4; glycogen; glycogen synthase; animal; comparative study; exercise; female; genetics; glucose blood level; metabolism; mouse; mouse strain; outbred strain; phenotype; skeletal muscle; time; Animals; Animals, Outbred Strains; Blood Glucose; Female; Glucose Transporter Type 4; Glycogen Synthase; Mice; Mice, Inbred Strains; Muscle, Skeletal; Phenotype; Physical Exertion; Time Factors; Mus; Mus musculus domesticus